Persepsi Mahasiswa Melalui Dialog Prodi Terhadap Peningkatan Kualitas Pelayanan Pendidikan - Aprilia, Galeh (Green Publisher Indonesia, 2024)
This research is motivated by the fact that higher education in Indonesia is experiencing a paradigm shift towards a more participatory and inclusive approach. This article examines the importance of dialogue between students and study programs in improving the quality of educational services at the Faculty of Teacher Training and Education, University of Muhammadiyah Surakarta, especially in the Accounting Education Study Program. The purpose of this study is to describe the aspirations of students through dialogue study programs in improving the quality of services of the Accounting Education Study Program of the University of Muhammadiyah Surakarta. Using quantitative and qualitative descriptive approach methods, the source of data for this study is through questionnaires and interviews from students, lecturers, and structural in the study program with 147 respondents in this study. The study also used three different data sources. The data collection techniques used are questionnaires and interviews to collect data from students, lecturers, and structural in the study program. This study uses source triangulation and techniques to ensure the validity of qualitative data. The results of the study show that student satisfaction with learning facilities, laboratory facilities, and lecturer teaching is generally good, but there are several areas that need improvement, such as the condition of LCD, air conditioning, and laboratory cleanliness. Although the majority of students are satisfied with the material and teaching, there are complaints about teaching and assessment methods. The Independent Learning Independent Campus (MBKM) program is considered useful, but integration with lectures needs to be improved. Improvements in the socialization of scholarship information and evaluation of study program services are expected to increase student satisfaction and support their overall academic achievement. The validity of the qualitative data obtained through a questionnaire related to the condition of learning facilities in the lecture hall shows that 59.7% of students feel that the available facilities are good. For the completeness of the laboratory in the Accounting Education Study Program, as many as 56% of students are satisfied. Regarding student satisfaction with the learning delivered by lecturers, 53.3% of students expressed satisfaction. Meanwhile, 52.8% of students were satisfied with the lecture material presented. Regarding the service of the study program, 54.1% of students were also satisfied. The results of the questionnaire showed that 49.1% of students were very satisfied with the scholarship information service, while satisfaction with the academic advisor (PA) service was recorded at 43.4%. Finally, 50.3% of students expressed satisfaction with the thesis supervisor's services. Based on the questionnaire data obtained, in general, the level of student satisfaction with various aspects in the lecture environment tends to be good. The majority of students are satisfied with the learning facilities, laboratory equipment, delivery of lecture materials, and study program services. However, there are several aspects that need more attention, such as scholarship information services and academic guidance services. The results of this study show the level of student satisfaction with the quality of study program services. This aspiration can be used as a valuable input for study programs to make efforts to improve the quality of better services.